VD_FINDINFO HC / 2013 / 515 vom 15. August 2013 - VD Tribunal cantonal (2013)
FRAIS DE LA PROCÉDURE, FRAIS JUDICIAIRES, DÉPENS, TRANSACTION JUDICIAIRE, ÉQUITÉ | 107 al. 1 let. a CPC (CH), 109 al. 2 let. a CPC (CH), 241 CPC (CH)